1994
DOI: 10.1177/019874299402000103
|View full text |Cite
|
Sign up to set email alerts
|

Video Self-Modeling and Cooperative Classroom Behavior in Children with Learning and Behavior Problems: Training and Generalization Effects

Abstract: This study investigated the effects of an instructional package incorporating videotaped self-assessment, self-modeling, discrimination training, and behavioral rehearsal on the cooperative classroom behavior of two second-grade children with learning and behavior problems. Observations were made of selected classroom behaviors in three different classes each day. Results indicate that the intervention was effective in helping young children acquire cooperative classroom behaviors, generalize these behaviors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 11 publications
5
20
0
Order By: Relevance
“…Findings are consistent with an extensive body of literature in video modeling with students with emotional and behavioral disorders (Falk et al, 1996;Kern-Dunlap et al, 1992;Lonnecker et al, 1994;O'Reilly et al, 2005). Similar to Lonnecker et al, video modeling promoted cooperative classroom behavior among students with learning problems.…”
Section: Discussionsupporting
confidence: 88%
“…Findings are consistent with an extensive body of literature in video modeling with students with emotional and behavioral disorders (Falk et al, 1996;Kern-Dunlap et al, 1992;Lonnecker et al, 1994;O'Reilly et al, 2005). Similar to Lonnecker et al, video modeling promoted cooperative classroom behavior among students with learning problems.…”
Section: Discussionsupporting
confidence: 88%
“…Positive results have been obtained for treating depression (Kahn, Kehle, Jenson, & Clark, 1990), stuttering (Bray & Kehle, 1996), elective mutism (Pigott & Gonzales, 1987), attention disorders (Dowrick & Raeburn, 1977;Woltersdorf, 1992), behavior disorders (Lasater & Brady, 1995), and aggressive behaviors (Buggey, 2007;Creer & Miklich, 1970;McCurdy & Shapiro, 1988). Likewise, VSM has proven to be efficacious as a tool for teaching skills such as math (Schunk & Hanson, 1989), life skills (Miklich, Chida & Danker-Brown, 1977), social behaviors (Bellini, Akullian, & Hopf, 2007;Lonnecker, Brady, McPherson, & Hawkins, 1994;Rasing, Coninx, Duker, & Van Den Hurk, 1994), and language (Buggey, 1995(Buggey, , 2005Haarmann & Greelis, 1982;Sherer et al, 2001;Wert & Neisworth, 2003;Whitlow & Buggey, 2003). In a review of 27 studies using VSM (Meharg & Woltersdorf, 1990), moderate to dramatic gains were reported across all target behaviors.…”
mentioning
confidence: 99%
“…Positive results have been obtained for treating depression (Kahn, Kehle, Jenson, & Clark, 1990), stuttering (Bray & Kehle, 1996), elective mutism (Pigott & Gonzales, 1987), attention disorders (Dowrick & Raeburn, 1995;Woltersdorf, 1992), behavior disorders (Lasater & Brady, 1995), and aggressive behaviors (Creer & Miklich, 1970;McCurdy & Shapiro, 1988). Likewise, VSM has proved efficacious as a tool for teaching skills such as math (Schunk & Hanson, 1989), life skills (Miklich, Chida, & DankerBrown, 1977), social behaviors (Lonnecker, Brady, McPherson, & Hawkins, 1994;Rasing, Coninx, Duker, & Van Den Hurk, 1994), and language (Buggey, 1995a;Haarmann & Greelis, 1982;Sherer et al, 2001;Whitlow & Buggey, 2003;Yingling & Neisworth, 2003). In a review of 27 studies using VSM (Meharg & Woltersdorf, 1990), moderate to dramatic gains were reported across all target behaviors.…”
mentioning
confidence: 99%